2014
DOI: 10.1002/cbic.201402577
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining‐Directed Activation of a Silent Angucycline Biosynthetic Gene Cluster in Streptomyces chattanoogensis

Abstract: Genomic sequencing of actinomycetes has revealed the presence of numerous gene clusters seemingly capable of natural product biosynthesis, yet most clusters are cryptic under laboratory conditions. Bioinformatics analysis of the completely sequenced genome of Streptomyces chattanoogensis L10 (CGMCC 2644) revealed a silent angucycline biosynthetic gene cluster. The overexpression of a pathway-specific activator gene under the constitutive ermE* promoter successfully triggered the expression of the angucycline b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…As demonstrated above, ScnA and ScnB are the natamycin efflux transporters whose genes are located within the biosynthetic gene cluster whereas Mfs1 and NepI/II act as complementary transporters whose genes are located outside the gene cluster. It has been suggested that there are 34 putative secondary metabolite biosynthesis gene clusters in the genome of S. chattanoogensis L10 (Zhou et al ., ), but mfs1 and nepI/II are not located in any of these clusters either. This suggests that instead of being acquired through horizontal gene transfer, mfs1 and nepI/II are original genes in the genome.…”
Section: Resultsmentioning
confidence: 84%
“…As demonstrated above, ScnA and ScnB are the natamycin efflux transporters whose genes are located within the biosynthetic gene cluster whereas Mfs1 and NepI/II act as complementary transporters whose genes are located outside the gene cluster. It has been suggested that there are 34 putative secondary metabolite biosynthesis gene clusters in the genome of S. chattanoogensis L10 (Zhou et al ., ), but mfs1 and nepI/II are not located in any of these clusters either. This suggests that instead of being acquired through horizontal gene transfer, mfs1 and nepI/II are original genes in the genome.…”
Section: Resultsmentioning
confidence: 84%
“…Another cryptic angucycline cluster is the chattamycin biosynthetic gene cluster. Although there is ovmZ orthologous in this cluster, the direct effector of regulation seems to be another positive regulator, ChaI, because the transcription of the cluster could be activated by constitutive expression of ChaI (11). Thus, it would be more complicated to activate cryptic gene clusters for angucycline antibiotics by manipulating the CSR genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a giant type I modular PKS gene cluster of Streptomyces ambofaciens ATCC23877 spanning almost 150 kb was activated by overexpression of a LAL family regulatory gene, leading to the discovery of stambomycins, unusual glycosylated macrolides with unique chemical structures and promising antiproliferative activity against human cancer cell lines (10). Similarly, the production of chattamycins A and B in Streptomyces chattanoogensis was activated by overexpression of a pathway-specific activator gene chaI (11). Disruption of a putative repressor gene, pgaY, activated the production of UWM6 and rabelomycin in Streptomyces sp.…”
mentioning
confidence: 99%
“…An angucycline-like antibiotic, chattamycin biosynthetic gene cluster was identified to be silent in S. chattanoogensis L10 and it was subsequently activated by overexpression of the gene chaI encoding the putative pathway-specific activator. This led to the identification of the angucycline antibiotics, chattamycins A and B (71-72) (Zhou et al, 2015).…”
Section: Molecular Elicitationmentioning
confidence: 99%